Cardiac computed tomography angiography‐derived analysis of left atrial appendage morphology and left atrial dimensions for the prediction of atrial fibrillation recurrence after pulmonary vein isolation. Issue 11 (14th October 2021) - Straube, Florian; Pongratz, Janis; Hartl, Stefan; Brueck, Benedikt; Tesche, Christian; Ebersberger, Ullrich; Helmberger, Thomas; Crispin, Alexander; Wankerl, Michael; Dorwarth, Uwe; Hoffmann, Ellen
Abstract: Background: Left atrial appendage (LAA) is a potential source of atrial fibrillation (AF) triggers. Hypothesis: LAA morphology and dimensions are associated with AF recurrence after pulmonary vein isolation (PVI). Methods: From cardiac computed tomography angiography (CCTA), left atrial (LA), pulmonary vein (PV), and LAA anatomy were assessed in cryoballoon ablation (CBA) patients. Results: Among 1103 patients undergoing second‐generation CBA, 725 (65.7%) received CCTA with 473 (42.9%) qualifying for detailed LAA analysis (66.3 ± 9.5 years). Symptomatic AF reoccurred in 166 (35.1%) patients during a median follow‐up of 19 months. Independent predictors of recurrence were LA volume, female sex, and mitral regurgitation ≥°II. LAA volume and AF‐type were dependent predictors of recurrence due to their strong correlations with LA volume. LA volumes ≥122.7 ml (sensitivity 0.53, specificity 0.69, area under the curve [AUC] 0.63) and LAA volumes ≥11.25 ml (sensitivity 0.39, specificity 0.79, AUC 0.59) were associated with recurrence. LA volume was significantly smaller in females. LAA volumes showed no sex‐specific difference. LAA morphology, classified as windsock (51.4%), chicken‐wing (20.7%), cactus (12.5%), and cauliflower‐type (15.2%), did not predict successful PVI (log‐rank; p  = 0.596). Conclusions: LAA volume was strongly correlated to LA volume and was a dependent predictor of recurrence after CBA. Main independent predictors were LA volume, female sex, and mitral regurgitation ≥°II. Gender differences in LA volumes were observed. Individual LAA morphology was not associated with AF recurrence after cryo‐PVI. Our results indicate that preprocedural CCTA might be a useful imaging modality to evaluate ablation strategies for patients with recurrences despite successful PVI.